(3HjGf GdMb HVeGf GdUObs - (3CHh GdYHGS GddhcQjs ((3GUagGf s)
(3ChdgG (B:s
(3GdMeO ddg ceG gh Cgdg gPG GdLRA GdKGfi ef GdcJGH GdeDda GdPi SejfGg cJGH HjGf GdMb HVeGf GdUOb GdcJGH GdChd ef GdWHjYGjJ ai HjGf eYGf cJGH GdSeGY GdWHjYi s
(3BNQgG (B:s
(3cJGH GdMjhGf Je cJGH GdMjhGf hHJeGeg JeJ GdWHjYjGJ s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3GfXQ GdeNWhW Qbe (B53s
(3GNJUQ gPG GdcJGH ef cJH GdQFjS GHf SjfG jTJed Ydi YOI cJHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs